The Wicker Man the official story of the film - Walsh, John 1971- (Titan Books, a division of Titan Publishing Group Ltd, 2023)
The wicker man is one of the greatest horror movies of all time--a chilling exploration of an isolated community with a terrible secret. Featuring a stellar cast including Christopher Lee, Edward Woodward, Britt Ekland and Ingrid Pitt, The wicker man has terrified audiences world-wide for fifty years. Author and filmmaker John Walsh tells the story of how this singular--and somewhat unlikely--folk-horror classic came to be, illustrated with fascinating behind-the-scenes photography, new interviews, exclusive artwork, and never-before-seen material from the StudioCanal archives. Learn the secret history of Summerisle, if you dare...